Study of the impacts of regulations affecting the acceptance of Integrated Community Energy Systems: public utility, energy facility siting and municipal franchising regulatory programs in Connecticut. Preliminary background report - Feurer, D. A.; Weaver, C. L.; Gallagher, K. C.; Hejna, D.; Rielley, K. J. (Ross, Hardies, O&#x27, 1980)
The Connecticut statutes expressly provide for the regulation of public utilities. As of January 1, 1979, responsibility for the regulation of utilities is vested in the Public Utilities Control Authority (PUCA). Formerly such authority was exercised by the Public Utilities Commission which has been abolished and replaced by the PUCA. The Public Utilities Act provides that the PUCA is to consist of five members appointed by the governor with the advice and consent of both houses of the general assembly. It should be noted that statutory references to the Public Utilities Commission are deemed to mean the Public Utilities Control Authority. The statute gives only a minor role to local government in regulating public utilities. Public utility regulatory statutes, energy facility siting programs, and municipal franchising authority are examined to identify how they may impact on the ability of an organization, whether or not it be a regulated utility, to construct and operate an ICES.